2012
DOI: 10.1038/modpathol.2011.163
|View full text |Cite
|
Sign up to set email alerts
|

From PTEN loss of expression to RICTOR role in smooth muscle differentiation: complex involvement of the mTOR pathway in leiomyosarcomas and pleomorphic sarcomas

Abstract: Over the past decade, comprehensive genomic studies demonstrated that leiomyosarcomas and most of the tumors previously labeled as 'malignant fibrous histiocytomas' share complex karyotypes and genomic profiles, and can be referred to as 'sarcomas with complex genomics'. We recently reported a series of 160 sarcomas with complex genomics such as leiomyosarcomas, myxofibrosarcomas, pleomorphic liposarcomas/ rhabdomyosarcomas and undifferentiated pleomorphic sarcomas. These tumors present with a frequent loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 39 publications
2
28
0
1
Order By: Relevance
“…Sequencing analysis revealed 1 out of the 5 cell lines, GCT, had a biallelic missense mutation (C>T) in exon 6 of PTEN, which produces a change in the amino acid sequence from glycine to leucine (aa 204), and was associated with loss of PTEN protein expression. These findings are consistent with those of other studies, which have similarly shown PTEN gene alterations to be infrequent in sarcoma (27)(28)(29). For example, a study reported PTEN mutation was at a low rate of 2.3% in 86 STS tumour samples (30).…”
Section: Discussionsupporting
confidence: 92%
“…Sequencing analysis revealed 1 out of the 5 cell lines, GCT, had a biallelic missense mutation (C>T) in exon 6 of PTEN, which produces a change in the amino acid sequence from glycine to leucine (aa 204), and was associated with loss of PTEN protein expression. These findings are consistent with those of other studies, which have similarly shown PTEN gene alterations to be infrequent in sarcoma (27)(28)(29). For example, a study reported PTEN mutation was at a low rate of 2.3% in 86 STS tumour samples (30).…”
Section: Discussionsupporting
confidence: 92%
“…To further portray the association between STSs and the MEF2 signature, we applied a statistical analysis to determine the correlation values, in terms of expression levels, between the 25 MEF2 targets and genes influencing their expression, including MEF2s, class IIa HDACs, and PTEN, using two data sets (40,41). Among the MEF2 family members, MEF2C shows the highest expression in STSs.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the Western blot and immunohistochemistry results were concordant in 23 out of 43 cases (53%), with discrepancies in 20 cases (47%) for the 46 samples with good data in both cases, and that Western blot results were more correlated with array comparative genomic hybridization status than immunohistochemistry (Gibault et al, 2011). Furthermore, they found that some tumors like T19, that are homozygously deleted for PTEN and lack mRNA or protein expression on Affymetrix and Western blot data, displayed a strong signal on immunohistochemistry, in several independent experiments (Gibault et al, 2011). Therefore, when there is a conflict between the Western blot analysis and IHC, the IHC data should be used with caution before ruling out technical bias in IHC such as nonspecific staining.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancies between immunohistochemistry and Western blotting for certain antibodies are not unexpected, as antigenic epitopes could change in different ways dependent on denaturing conditions, for example, formalin and SDS-PAGE, resulting in changes of antibody specificity between Western blot and IHC for certain antibodies. For example, Gibault et al (2011) assessed 57 sarcomas by Western blot analysis and analyzed their correlation with array comparative genomic hybridization and immunohistochemistry results. They found that the Western blot and immunohistochemistry results were concordant in 23 out of 43 cases (53%), with discrepancies in 20 cases (47%) for the 46 samples with good data in both cases, and that Western blot results were more correlated with array comparative genomic hybridization status than immunohistochemistry (Gibault et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation